THE EVALUATION OF YARN MOVEMENT IN THE SPIN BOX - Sherzod Korabayev; Guzal Jabborova (Journal Park Publishing, 2022)
The rotor plays a crucial role in the spinning process, responsible for transporting the fibres in the airflow channel, transferring the fibres to the inside of the rotor, and helping to collect the fibres in the rotor shaft. At the same time, the airflow can also interfere with fibre orientation, resulting in poor yarn quality. In the article, research on the movement of yarn in the spinning chamber is studied and analyzed.
Keywords: airflow field, optimization of rotor spinning, computational fluid dynamics, spinning machine, camera.